EFEKTIVITAS PROGRAM BANTUAN LANGSUNG TUNAI DANA DESA DI DESA PADANG BINJAI KECAMATAN TETAP KABUPATEN KAUR - Purnawan, Heru; Mardianto, Mardianto; Noviyanto, Hernowo; Darmawi, Edi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Prof Dr Hazairin, SH, 2023)
The aim of this research is to determine the effectiveness of the Direct Cash Assistance Program of the Village Fund in Padang Binjai Village, Constanta Sub-District, Kaur District. To address this issue, the researcher used a qualitative descriptive research method. The research results indicate that the effectiveness of the Direct Cash Assistance Program of the Village Fund in Padang Binjai Village, Constanta Sub-District, Kaur District is effective based on 1) the success of the Village Fund Direct Cash Assistance program in terms of implementation. The process of the Village Fund Direct Cash Assistance program is 2) Achieving the targets set by the government, where the Village Fund Direct Cash Assistance in Padang Binjai Village meets the criteria set by the government. 3) Satisfaction with the program, where the Latimojng village community is very satisfied with this program because it is very helpful to the community, 4) Output and input levels, where government expectations match the results achieved by the community, 5) Achieving the general objective, implementing the BLT-DD program objectives accurately.